2015
DOI: 10.1007/s11307-015-0868-y
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Cardiac Self-Gating of Small-Animal PET Data

Abstract: Purpose: The cardiac gating signal (CGS) in positron emission tomography (PET) studies is usually obtained from an electrocardiography (ECG) monitor. In this work, we propose a method to obtain the CGS in small-animal PET using the acquired list-mode data without using any hardware or end-user input. Procedures: The CGS was obtained from the number of coincidences over time acquired in the lines-of-response connected with the cardiac region. This region is identified in the image as its value changes with freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A novel respiratory gating method was proposed by Todica et al in which the alterations in the amplitude of the ECG signal and heart-beat variations during the breathing cycle of the rat heart scan have been detected and utilized as respiratory triggered signal to improve quantitative values [107]. Herraiz et al proposed a data-driven approach for automatic gating in small animal cardiac imaging which involves analyzing the count-rate variation of the heart in the frequency domain [94].…”
Section: D Image Reconstruction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel respiratory gating method was proposed by Todica et al in which the alterations in the amplitude of the ECG signal and heart-beat variations during the breathing cycle of the rat heart scan have been detected and utilized as respiratory triggered signal to improve quantitative values [107]. Herraiz et al proposed a data-driven approach for automatic gating in small animal cardiac imaging which involves analyzing the count-rate variation of the heart in the frequency domain [94].…”
Section: D Image Reconstruction Methodsmentioning
confidence: 99%
“…Moreover, it has been demonstrated that positron range effect depends significantly upon the physical properties of the medium and surrounding tissues. This has spurred the interest towards more accurate methods like CT-based tissue-dependent spatially-variant models which ultimately render artifact-free images, improved quality and better tumor delineation when using high-energy radioisotopes such as 68 Ga [87,94].…”
Section: Resolution Recovery Image Reconstructionmentioning
confidence: 99%
“…Previously, only the left ventricle was used as the region of interest to reduce the motion of heart and improve the precision. Recently, Herraiz et al (2016) and Verhaeghe et al (2018) showed that the left ventricle volume can be estimated by means of cardiac gating during PET acquisition. For this purpose, PET raw data were divided into time subsets according to the different phases of the heart activity.…”
Section: Kinetic Modeling (Logan and 2tcm Analysis)mentioning
confidence: 99%